Creative Industries’ Entrepreneurial Success: Social Capital, Networks, and Internationalization Strategy - Ado, Abdoulkadre; Diamouténé, Massa Idriss (Journal of Comparative International Management, 2023)
The purpose of this study is to explain the success factors of business ventures in creative industries. By analyzing three types of festivals in three countries through the perspectives of entrepreneurial success, internationalization, and management, the paper explains how business ventures in creative industries from developing economies mobilized key factors to succeed. The study particularly focuses on identifying the types of partners, channels, and strategies that entrepreneurs in creative industries mobilized to achieve international success. Using data from publicly available online sources to categorize important factors for success, the paper argues that social capital-based view may explain success in creative industries better than resource-based or knowledge-based views although the combination of the three perspectives is deemed necessary. Founders’ personal social capital (connections and networks) appeared particularly important for entrepreneurial success in creative industries. The importance of social capital is perceivable in national and international success and is also applicable, to some degree, to the contexts of both developing and developed economies.